Report of job done on preventing ransomware virus attack to PC - Mustafa, mohd mizam; Ayob, Mohd Fairullazi (2017)
This paper is prepared and deliberated in Kulliyyah management meeting to provide steps and actions to protect all desktop computers in KAED including ICT labs, teaching venues and administrator office from Ransomware attack.